Finite-element design and analysis of switched reluctance motor for automobile applications - Raj, E. Fantin Irudaya; Appadurai, M.; Rani, E. Francy Irudaya; Jenish, I. (Multiscale and Multidisciplinary Modeling, Experiments and Design, 2022)
In recent times, the electric vehicle (EV) has attracted more consumers worldwide. The engineers also try to develop an efficient and economical EV for consumers. The efficiency and performance of EV are purely based upon the electric propulsion system, which is adopted. Due to some of the disadvantages of the motor drives presently used, the engineers try to identify the good and efficient alternative. In this context, the switched reluctance motor (SRM) can be considered for EV applications because of its simple and robust construction. The present work uses a finite-element software package called “Motorsolve” and MATLAB/SIMULINK environment to design a three-phase 12/8 SRM (SRM with 12 stator and 8 rotor poles). A comparison is made between 12/8 SRM and its other variant 6/4 SRM in terms of torque ripples. In addition, it is also compared with other motor drives commonly used in EV applications in terms of weight/power ratio and weight/torque ratio. Results show that the proposed three-phase 12/8 SRM has a low torque ripple than the 6/4 SRM configuration, and it is more suited for EV applications. It also has a low weight/power ratio and weight/torque ratio compared with other motor drives commonly used in EV.